PENJATUHAN HUKUMAN DISIPLIN BERDASARKAN PERATURAN PEMERINTAH TENTANG DISIPLIN PEGAWAI NEGERI SIPIL : Disciplinary Punishment Based on Government Regulations Regarding The Discipline of Civil Servants - Phinesia, Elizabeth Liely; Pamungkas, Yogo (AMICUS CURIAE, 2024)
The mechanism for imposing disciplinary punishment for Civil Servants is a process that must be passed before being sentenced to disciplinary punishment by an official authorized to punish including summons, examination, sentencing and delivery of decisions. The problem in this study is the process of examining and imposing disciplinary punishment on Ridwan Yasin and the legal consequences. To answer these problems, a normative juridical research type is carried out which is analytical descriptive in nature. The data used are secondary data with primary legal materials, secondary and tertiary obtained through library research. The data that has been obtained from the results of further research will be analyzed using qualitative methods and drawing conclusions by deductive way. From the results of the study it can be concluded that the imposition of disciplinary punishment on Ridwan Yasin in the Decree of the North Gorontalo Regent Number: 800/BKPP/2097/IX/2021 was declared procedurally and substantially flawed.